English Impact Of Counseling Using Video Media On Understanding Of Healthy Pregnancy Planning Among Women Of Childbearing Age - Linda Trisna Dewi Ni Luh Putu; Ni Wayan Suarniti; Ni Gusti Kompiang Sriasih (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2025)
Abstract Introduction: The risk of termination of pregnancy, which can lead to adverse health outcomes, can be minimized through proper pregnancy planning. Women of childbearing age play a crucial role in this process, requiring effective educational interventions. This study aims to examine the effect of video-based counseling on the knowledge of healthy pregnancy planning among women of childbearing age in Satra Village, Klungkung Regency. Method: This pre-experimental study employed a one-group pretest-posttest design to evaluate changes in knowledge before and after the intervention. The study involved 58 respondents selected through proportional random sampling. A structured questionnaire was utilized as the research instrument to assess participants' knowledge levels before and after the intervention. The normality of the data was tested using Kolmogorov-Smirnov, which revealed non-normal distribution (p < 0.05). Consequently, the Wilcoxon Signed Rank Test was employed for bivariate analysis. Results: The median pre-test knowledge score was 58.00, increasing to 84.00 in the post-test, indicating a significant improvement. The Wilcoxon Signed Rank Test yielded a Z value of -6.522 and a p-value of 0.000 (p < 0.05), confirming a statistically significant difference in knowledge levels after video-based counseling. Conclusion: The findings demonstrate that video media is an effective tool for improving knowledge about healthy pregnancy planning, offering clear and accessible information. It is recommended that Community Health Centers integrate video-based approaches into broader health education initiatives. Future research could benefit from incorporating larger samples, control groups, and longitudinal designs to assess sustained behavioral impacts. Keywords: Healthy Pregnancy Planning; Knowledge Improvement; Video-Based Counseling; Women of Childbearing Age